Broadband Microwave-Based Metrology Platform Development: Demonstration of In-Situ Failure Mode Diagnostic Capabilities for Integrated Circuit Reliability Analyses. (7th November 2014) - You, Lin; Okoro, Chukwudi A.; Ahn, Jung-Joon; Kopanski, Joseph; Franklin, Rhonda R.; Obeng, Yaw S.
Abstract : In this paper, we discuss the use of broadband high frequency electromagnetic waves (RF) to non-destructively identify, classify and characterize performance-limiting defects in emerging nanoelectronic devices. As an illustration, the impact of thermal cycling on the RF signal characteristics (insertion loss (S21 ) and return loss (S11 )) is used to infer thermo-mechanical stress-induced defects in metal interconnects. The inferred defects are supported with physical analytical data where possible.